'Policy traction' on social and emotional wellbeing: comparing the education systems of England, Wales, Scotland and Northern Ireland. Issue 4 (2nd October 2022) - Donnelly, Michael; Brown, Ceri
ABSTRACT: This paper provides a 'home international' comparative analysis of education policy on social and emotional wellbeing, drawing on the case of the UK and its four distinct education systems of England, Wales, Scotland and Northern Ireland. Wales, Scotland and Northern Ireland have developed more holistic policy in this area, which stands in stark contrast to the disparate policies of England. These divergences in policy are likely to account for differences observed in the awareness, perceived value and 'take up' of policy by schools – what we refer to here as differences in 'policy traction' between the different systems of education. Wales, Scotland and Northern Ireland had the highest rates of 'policy traction' compared to England where schools appeared adrift about policy in their jurisdiction. We consider these findings in light of challenges and opportunities for policy learning.